Group B streptococcal disease in the mother and newborn—A review. (September 2020) - Steer, Philip J.; Russell, Alison Bedford; Kochhar, Sonali; Cox, Philippa; Plumb, Jane; Gopal Rao, Gopal
Highlights: Antenatal testing and intrapartum antibiotic prophylaxis (IAP) with penicillin has reduced the incidence of invasive neonatal Group B streptococcus disease by up to 80%. Countries persisting with a 'risk based' approach to IAP have not seen similar falls, and in some cases (e.g. the UK) have seen a rise in the incidence of disease. Intrapartum antibiotic prophylaxis produces short-term alterations in the neonatal microbiome, but none so far are considered to be of clinical significance. The cornerstone of neonatal care remains prompt recognition of signs of infection and administration of benzylpenicillin and gentamicin, pending culture results. A vaccine against GBS infection would have many advantages but there are still many barriers to be overcome before one becomes available. Abstract: Group B Streptococcus, a common commensal in the gut of humans and in the lower genital tract in women, remains an important cause of neonatal mortality and morbidity. The incidence of early onset disease has fallen markedly in countries that test women for carriage at 35–37 weeks of pregnancy and then offer intrapartum prophylaxis with penicillin during labour. Countries that do not test, but instead employ a risk factor approach, have not seen a similar fall. There are concerns about the effect on the neonatal microbiome of widespread use of antibiotic prophylaxis during labour, but so far the effects seem minor and temporary. Vaccination against GBS would be acceptable to most women and GBS vaccines are in the early stages of development. Tweetable abstract : Group B Strep is a key cause of infection, death and disability in young babies. Antibiotics given in labour remain the mainstay of prevention, until a vaccine is available.